Generation of Induced Pluripotent Stem Cell-Like Lines from Human Pancreatic Ductal Adenocarcinoma - Kim, Jungsun; Zaret, Kenneth S (Methods in molecular biology (Clifton, N.J.), 2019)
Pancreatic ductal adenocarcinoma (PDAC) has a dismal prognosis, mainly because the tumors are detected too late for effective treatment or for developing suitable therapeutics. Reprogramming cancer cells to pluripotency by induced pluripotent stem cell (iPSC) technology, which can be then programmed back to their original cellular state, allows for studying the dynamic events in the course of the disease progression. Thus, we applied iPSC technology to model early progression of PDAC. We showed that when an iPS-like cell line, designated 10-22, derived from human recurrent PDAC, was injected into immunodeficient mice, the cells consistently recapitulated preinvasive, pancreatic intraepithelial neoplasia (PanIN) to invasive stages of human PDAC. This model was recently validated by revealing a new biomarker that can classify early resectable PDAC patients from healthy subjects. The procedure to derive iPSCs from human PDAC is principally the same as the procedure to generate iPSCs from normal human fibroblast. However, the heterogeneous initial populations, different cellular states, and active memory of pancreatic epithelial cells challenge for making iPSC-like lines from human PDAC. Herein, we describe how to create and maintain iPSC-like line from human PDAC by lentiviral transduction of reprogramming factors.